Proposed conservation of the name Penthe Newman, 1838 (Coleoptera: Tetratomidae: Penthinae) threatened by the discovery of an older available name - Bouchard, Patrice; Pollock, Darren A. (Zootaxa, 2009)
Penthe Newman, 1838 includes nine species distributed in China, the Himalayas, Japan, the Oriental Region and North America (Nikitsky, 1998; Young & Pollock, 2002) and is the type genus of the tetratomid subfamily Penthinae Lacordaire, 1859. Like many other obscure members of Tenebrionoidea, Penthe has had an unsettled family placement until recently. Most early authors placed the genus in Tenebrionidae (e.g. Newman, 1838; Melsheimer, 1853). Then, there was a period during which it was most often placed in Melandryidae, either in Melandryini (e.g. LeConte & Horn, 1883), Penthini (Woodruff, 1920), or Tetratomini (e.g. Csiki, 1924). Finally, based on both larval and adult characters, Penthe was placed in Tetratomidae (e.g. Crowson, 1955; Lawrence, 1982; Nikitsky, 1998). Adults and larvae feed on various fungi associated with rotting wood, e.g. Polyporus, Piptoporus, and Fomitopsis (Lawrence, 1991). As mentioned below, the name Penthe has been used uniformly in the various catalogues, checklists and treatments of North American Coleoptera since Newman’s original description in 1838.